Cuneanes as Potential Benzene Bioisosteres Having Chirality - Takebe, Hiyori; Matsubara, Seijiro (Synthesis, 2024)
Cuneane, a structural isomer of cubane, possesses C2v symmetry, unlike the Oh symmetry of cubane. It can exhibit chirality with only a single substituent, differentiating it from cubane. Consequently, cuneane is being explored as a potential benzene bioisostere in pharmaceutical molecules, adding complexity such as chirality through isomerization of the cubane skeleton. Although there has been limited research on the synthesis of cuneane, recent years have seen increased attention devoted to this cage hydrocarbon. In this short review, we will discuss recent advances in the synthesis, utilization, and transformations of the cuneane framework into other cage hydrocarbons.1 Introduction: Absolute Configuration Notation2 Preparation of 1,3- and 2,6-Disubstituted Cuneanes by Constitutional Isomerization of 1,4-Disubstituted Cubanes3 Preparation of 1,2-Disubstituted Cuneanes from 1-Cuneanecarboxamide via Directed ortho-Metalation4 Investigation of the Potential as a Benzene Bioisostere5 Asymmetric Synthesis of Cuneanes6 Cuneane Scaffold Editing7 Conclusion
Keywords: cuneane; cubane; benzene bioisostere; chirality; asymmetric synthesis